Seasonal abundance of commercially important shrimp seed in the Mulki Estuary, south-west coast of India - Naik, Manja; Benakappa, S; Rajesh, K M; Rajesh, Mridula (Indian Journal of Fisheries, 2011)
Shrimp seed of five commercially important penaeid species viz., Fenneropenaeus indicus, Fenneropenaeus merguiensis, Peneaus monodon, Metapenaeus monoceros and Metapenaeus dobsoni were encountered in the Mulki Estuary during the present investigation. F. indicus was predominant in the samples in the early pre-monsoon period (25 to 28.3%) and late post-monsoon period (18.2 to 21.4%) at all the stations. F. merguiensis seed showed distinct variations and was dominant during pre-monsoon months (30 to 89.3%) whereas P. monodon seed was predominant during early pre-monsoon season (22.1 to 26.6%) at all the stations. Both M. dobsoni and M. monoceros were dominant during the later part of post-monsoon season (22.1 to 26.6%; 9.8 to 47.6% respectively). Among the hydrographical parameters tested salinity (r = 0.6954) and temperature (r = 0.7307) showed significant positive correlation with shrimp seed availability in the Mulki Estuary.